A mirage turned into reality: strategies and socio-cultural representations of a group of East Timorese students in Portugal and the return home - Cristovão, Dalia (2013)
During two years (between February 2009 and February 2011), a group of ten East Timorese students took up residence in Evora (Portugal), in order to pursue their postgraduate studies. In this period they lived a reality with different characteristics from the ones they knew, at a cultural, linguistic and academic level. Through narrative analysis of their testimony we intend to explore the individual and social dimension of this experience, including their life courses, expectations and socio-cultural representations. Some of the factors that often are associated with the choice of a host country for further studies, such as cultural, linguistic, geographical proximity, or even the quality of life (IMO, 2008), were not considered in this case. On the contrary, the language issue revealed itself to be a major obstacle. The motivation of these students was the importance of “grab” the opportunity (scholarship, obtaining a master’s degree), regardless the difficulties they were about to face, or even without having a clear notion of the possible difficulties. All of them completed the master degree on the required period of time; however, the diminute dominance of the Portuguese language was clearly a factor of impoverishment of the international student mobility experience, not only at an academic level but also in socio-cultural terms. While at academic level they were exposed to an additional effort to obtain approval, at a social level.